2021
DOI: 10.1016/j.brs.2021.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Delta oscillation underlies the interictal spike changes after repeated transcranial direct current stimulation in a rat model of chronic seizures

Abstract: Background: Transcranial direct current stimulation (tDCS) provides a noninvasive polarity-specific constant current to treat epilepsy, through a mechanism possibly involving excitability modulation and neural oscillation. Objective: To determine whether EEG oscillations underlie the interictal spike changes after tDCS in rats with chronic spontaneous seizures. Methods: Rats with kainic acid-induced spontaneous seizures were subjected to cathodal tDCS or sham stimulation for 5 consecutive days. Video-EEG recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
1
3
0
1
Order By: Relevance
“…1F). Although comparison of the spectral bands before and after the IEDs in the theta (4-10 Hz), gamma (30-70 Hz) and high-frequency oscillations (80 – 160 Hz) bands showed no significant difference (theta p = 0.277, gamma p = 0.749, HFO p=0.338), likely due to the small number of sessions, the direction of changes (increased gamma power and decreased 80 – 160 Hz band power) was similar to those reported previously (Wu et al, 2021; Meisenhelter et al, 2021).…”
Section: Resultssupporting
confidence: 88%
“…1F). Although comparison of the spectral bands before and after the IEDs in the theta (4-10 Hz), gamma (30-70 Hz) and high-frequency oscillations (80 – 160 Hz) bands showed no significant difference (theta p = 0.277, gamma p = 0.749, HFO p=0.338), likely due to the small number of sessions, the direction of changes (increased gamma power and decreased 80 – 160 Hz band power) was similar to those reported previously (Wu et al, 2021; Meisenhelter et al, 2021).…”
Section: Resultssupporting
confidence: 88%
“…Results showed that recurrent c-tDCS reduced interictal spikes, increased low-frequency delta oscillation, decreased high-frequency gamma and beta oscillation, and lowered hippocampal brain-derived neurotrophic factor (BDNF) protein expression. These results suggest that c-tDCS have an inhibitory effect on neuronal excitability in the epileptic brain by enhancing the endogenous delta oscillation (42). In 2020, researchers examined the effect of tDCS on seizure severity, EEG activity, and post-SE outcomes in rats' kainic acid-induced SE model.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Antiepileptic therapies can cause side effects, such as rebound excitations, followed by the application of inhibitory stimuli. Acute rebound effects of AEDs [10,11], VNS, DBS [12][13][14], and TMS [15,16], are prolonged, probably because of neuronal plasticity [17,18]. The stimulus frequency [13,19,20] and length [21,22] are significant factors inducing rebound.…”
Section: Introductionmentioning
confidence: 99%
“…The stimulus frequency [13,19,20] and length [21,22] are significant factors inducing rebound. In electrical stimulations, brief stimuli can cause temporary rebound, followed by short inhibition [17,23]. Moreover, fast successive stimulations could exhaust GABA and reinforce excitatory effects, ultimately breaking inhibitory functions [2].…”
Section: Introductionmentioning
confidence: 99%